Emotions and identity - Zerbe, W. J.; Härtel, Charmine E. J., 1959-; Ashkanasy, Neal M., 1945-; Petitta, Laura (Research on emotion in organizations, 2017)
This volume focuses on the role of emotions in forming and sustaining identities at work, and the value of exploring these topics from various theoretical and methodological points of view. This volume recognizes the depth of emotion and identity at work by addressing these topics on individual, occupational, and social role levels.